2020
DOI: 10.1001/jamadermatol.2020.4097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Incidence Rate and Risk Factors for Keratoacanthoma Among Residents of Queensland, Australia

Abstract: IMPORTANCE Keratoacanthoma (KA) is a common and generally benign keratinocyte skin tumor. Reports of the incidence rates of KA are scant. In addition, the risk factors for KA are not well understood, although associations with UV radiation exposure and older age have been described. OBJECTIVETo investigate the incidence rate of KA and the risk factors for developing KA. DESIGN, SETTING, AND PARTICIPANTS The study included data from 40 438 of 193 344 randomly selected residents of Queensland, Australia, who par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Generally, KA are benign keratinocyte skin tumours mostly seen in patients over 60 2 . In this young patient with two KA/cSCC, a sebaceoma, and a family history of digestive cancers, a genetic disease, such as a Muir‐Torre syndrome (MTS), was suspected 3–6 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Generally, KA are benign keratinocyte skin tumours mostly seen in patients over 60 2 . In this young patient with two KA/cSCC, a sebaceoma, and a family history of digestive cancers, a genetic disease, such as a Muir‐Torre syndrome (MTS), was suspected 3–6 .…”
Section: Discussionmentioning
confidence: 92%
“…Generally, KA are benign keratinocyte skin tumours mostly seen in patients over 60. 2 In this young patient with two KA/cSCC, a sebaceoma, and a family history of digestive cancers, a genetic disease, such as a Muir-Torre syndrome (MTS), was suspected. [3][4][5][6] MTS is a variant of hereditary non-polyposis colorectal cancer or Lynch syndrome, 7 which is an autosomal dominant disorder due to DNA mismatch repair (MMR) default including deleterious germline mutation of MLSH1, MSH2, MSH6 or PMS2.…”
Section: Discussionmentioning
confidence: 99%
“…Keratoacanthoma commonly erupts on sun exposed areas with signs of actinic damage. In a large prospective study, it was suggested that ultraviolet radiation, older age (≥60 years), male sex, smoking and high alcohol use are independent risk factors for the development of keratoacanthoma [2]. The exact etiology is uncertain but is believed to be multifactorial, including ultraviolet B radiation, genetic susceptibility, carcinogens, immunosuppression and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of literature on the aetiology of KA. Previous studies by us ( 10 ) and others ( 1 , 2 , 11 13 ) suggest that exposure to ultraviolet (UV) radiation plays a major role in development of KA. Other risk factors include male sex, older age, fair skin, smoking and high alcohol use ( 1 – 3 , 10 , 11 ).…”
mentioning
confidence: 98%
“…Previous studies by us ( 10 ) and others ( 1 , 2 , 11 13 ) suggest that exposure to ultraviolet (UV) radiation plays a major role in development of KA. Other risk factors include male sex, older age, fair skin, smoking and high alcohol use ( 1 – 3 , 10 , 11 ). KA has been reported to be 10–20 mm in size and to most commonly develop on the head, neck and upper extremities ( 14 21 ).…”
mentioning
confidence: 98%